Jesus and the Spirit in Paul’s Theology: The Earthly Jesus - Coulson, John R. (The catholic biblical quarterly, 2017)
A comprehensive understanding of Paul’s christological monotheism must account for what Paul says about God’s Spirit in Jesus’ earthly life. Based on an analysis of relevant Pauline passages, I argue that Paul knows and affirms the tradition of Jesus’ Spirit-anointing as God’s Son and also understands Christ as having been raised through the Spirit. But Paul does not draw particular attention to these things. He draws attention to the risen Lord, who, together with God the Father, is the source of the Spirit to believers (Rom 8:9; Gal 4:6). Although Paul does not have a Spirit christology, he does see Jesus’ Spirit-anointing as integral to Jesus’ sonship and messianic mission, and he sees Jesus in some respects as a pattern for God’s people in their experience of the Spirit. Finally, I propose how the humanity and divinity of Christ can be seen in relation to the Spirit within Paul’s christology.